A Oscilação Decadal do Pacífico (ODP) e sua influência nas temperaturas máximas e mínimas do Rio Grande do Sul - Omena, João Carlos Ribeiro (2010)
The Rio Grande do Sul is a State with characteristics in agriculture, that the basis of its economy. In addition, the State also receives many tourists in the region of tumuc and coast. These factors suffer influence of temperature and that a study is necessary to state that the economy is not affected. It is known that there is an ocean influence in meteorological variables and emphasizes that the Pacific Ocean is the largest of the oceans. The sea surface temperatures (SST) of the Pacific Ocean, have a configuration with long-term variations, similar to El Niño, called the Pacific Decadal Oscillation (PDO) and it was discovered that the PDO influences in precipitation in the State (Rebello, 2006). Objective is to study the possible influences of PDO maximum and minimum temperature. For this data used the maximum and minimum temperature from 1925 to 2008 surface stations INMET homogeneous temperature zones and PDO index. Anomaly calculations were made of average temperature minimum and average maximum for each station and their respective monthly averages. With these results calculated the PDO index percentile and the average maximum temperature anomalies and minimal. The percentile served to separate bands ranges below normal, up to 40%, between 40% and 60% being the transition track or normal and above 60% as above normal range. The contingency table was also used as a tool to better organize your data and separate them in cases of normal temperature, maximum below (T. Max. ( - )), normal, and above the normal (T.Max. ( + )) and the minimum temperature is below normal (T. Min. ( - )), normal, and above the normal (T. Min. ( + )). After the establishment of contingency table was necessary to calculate percentage results. For better orientation was done a climatology for each region homogeneous separated into upper and lower limits, where values that are within this limit are considered in the normal range. The test was done the Chi square and as a result it was noted that the invalidity of the test is true. It was possible to check this work in R1 the PDO warm influenced an increase maximum temperature and decrease minimum temperature; the cold PDO influenced in R2 an increase minimum temperature and warm PDO decrease maximum temperature and minumum temperature. Cold PDO influenced in R3 increase the maximum and minimum tmeperature and warm PDO decrease maximum temperature and increase minimum temperature; in R4 the cold PDO influenced an increase maximum and minimum temperature and the warm PDO decreased the maximum and minimum temperature. All these results are given in number of cases over the course of the year. However doesn t have significant among variables. So, the State Rio Grande do Sul maximum and minimum temperature are influencied by PDO but this was insignificant.